If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 24 + 3m = 32 Reorder the terms: 24 + 5m + 3m = 32 Combine like terms: 5m + 3m = 8m 24 + 8m = 32 Solving 24 + 8m = 32 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 8m = 32 + -24 Combine like terms: 24 + -24 = 0 0 + 8m = 32 + -24 8m = 32 + -24 Combine like terms: 32 + -24 = 8 8m = 8 Divide each side by '8'. m = 1 Simplifying m = 1
| 8a+6=6 | | 155=40t+55 | | x+4(x-3)=2(x-6)+9 | | F=40t+55 | | -6+10x=-4 | | -18n+4=-14n-16 | | 10z=12+7z | | 3*x+3=21 | | 4x(x-2)-3x(x+1)=18 | | C-7/3=-2 | | 84v+105=42v-126 | | (4x-6)/2=x^2-2x-24 | | 20bc^5*8b^2c= | | 20bc^5+8b^2c= | | 5w-15=3w-5 | | 5x+-8=13x | | 7x+9-2x=12-13x-14 | | -3m/7=-1 | | x^2+2x+1=6 | | 6t+19=7 | | 3(4a-b)-3(4b-2a)= | | (2w+5)(3-w)=0 | | 1.375=11 | | 6x-5=-22 | | -3(x+6)-44=2-49 | | 9x-20=8(x-1) | | 92y=7(13y+21) | | 16-13=x/-4 | | y+16=z | | 16-45=3(x-3)-5 | | 12x+(x-1)=96 | | -11+3=m-3 |